Apalutamide: Emerging Therapy for Non-Metastatic Castration-Resistant Prostate Cancer - Nora A. Alkhudair (Elsevier, 2019)
Prostate cancer is the second deadliest cancer in the US and the fourth most common cancer among Saudi males. Patients usually present with non-metastatic disease and treated with localized therapy. However, up to 40% of the patients will experience biochemical recurrence, within 10 years. Androgen deprivation therapy (ADT) is used in this setting to delay metastatic disease. Patients with high prostate-specific antigen (PSA), despite appropriate ADT, are diagnosed with castrate-resistant prostate cancer (CRPC). A subset of those patients will be presented with a shorter PSA doubling time (PSA-DT) ≤10 months. These patients are identified at higher risk for metastatic disease and death from prostate cancer, which represents a challenging dilemma where optimal management is unclear. Apalutamide was the first drug to get approved in the localized setting to delay metastatic disease from occurring. This review article will discuss the development, safety, and efficacy of apalutamide and its current place in therapy.